Pengaruh Audit Internal dan Akuntabilitas Suber Daya Manusia terhadap Perwujudan Good Governance pada Lembaga SKK Migas - Latifah Latifah; A. Rinto Pudyantoro (Jurnal Maksipreneur, 2015)
Special Unit for Upstream Oil and Gas Business Activities (SKK Migas) is an institution established by the Government of the Republic of Indonesia through Presidential Regulation (Perpres) No. 9 of 2013 on the Management of Upstream Oil and Gas Business Activities. The task of SKK Migas is to manage the upstream oil and gas business activities based on cooperation contracts. The purpose of the establishment of this institution so that retrieval of natural resources of oil and gas owned by the State can provide maximum benefit and acceptance for the state to the greatest prosperity of the people. Based on these tasks and objectives, SKK Migas is responsible to the state and all Indonesian people to work properly, honestly, fairly, cleanly, transparently and competently in order to achieve good governance of state institutions. Therefore, internal monitoring (internal audit) and accountability of its human resources are required. This research has a purpose to test the influence of internal audit and human resource accountability to the achievement of good governance at SKK Migas institution. This research uses survey method with population of all staffs of SKK Migas. Sampling method used is sampling with purposive sampling technique. In this study, 145 samples were taken. Methods of data collection was done by using questionnaires containing several questions with the method of data analysis using multiple regression. The result of this research is to accept both hypothesis which is internal audit have positive effect toward the achievement of good governance in SKK Migas. And the accountability of human resources positively affect the achievement of good governance in SKK Migas.